Antiepileptic Drug Exposure in Infants of Breastfeeding Mothers With Epilepsy - Frankie, Frankie; Muhammad Arief, Muhammad Arief; Florence, Florence (International Medical Journal Corp. Ltd, 2024)
Background: The literature on antiepileptic drug (AED) exposure in breastfeeding mothers with epilepsy reveals a complex interplay between the management of maternal health and the potential risks to infants. Research indicates that epilepsy occurs in approximately 0.3-0.7% of pregnancies, with AEDs being linked to congenital disorders and developmental impairments in newborns (Reza Najafi et al., 2012). The careful balancing of seizure control and fetal safety is paramount, as uncontrolled seizures can pose significant risks to both the mother and the fetus (Ikeda-Sakai et al., 2019). Literature Review: The implications of AED exposure extend to breastfeeding, where concerns about drug presence in breast milk must be weighed against the potential cognitive benefits of breastfeeding for infants (Khuda & Aljaafari, 2018). While some studies suggest that breastfeeding may confer advantages that outweigh the risks associated with AED exposure, healthcare providers must guide mothers on optimal feeding practices to minimize infant exposure (Khuda & Aljaafari, 2018). Folic acid supplementation emerges as a critical preventive strategy, particularly for women on AEDs, to mitigate the risk of neural tube defects and other developmental issues (Ikeda-Sakai et al., 2019). This underscores the necessity for ongoing education and counseling for women with epilepsy regarding their medication management and nutritional needs during pregnancy and breastfeeding (Kashif et al., 2019). Conclusion: In conclusion, the literature emphasizes the need for individualized care for women with epilepsy who are pregnant or breastfeeding. The potential risks associated with AED exposure must be carefully managed through expert consultation, ongoing monitoring, and the implementation of preventive strategies such as folic acid supplementation. Continued research is vital to better understand the long-term effects of AEDs on infant development and to inform clinical practice.